Control of laser plasma accelerated electrons for light sources - T. André (Nature Portfolio, 2018)
Electron beam quality in accelerators is crucial for light source application. Here the authors demonstrate beam conditioning of laser plasma electrons thanks to a specific transport line enabling the control of divergence, energy, steering and dispersion and the application to observe undulator radiation.